2015
DOI: 10.3390/md13063877
|View full text |Cite
|
Sign up to set email alerts
|

Ecklonia cava Polyphenol Has a Protective Effect against Ethanol-Induced Liver Injury in a Cyclic AMP-Dependent Manner

Abstract: Previously, we showed that Ecklonia cava polyphenol (ECP) treatment suppressed ethanol-induced increases in hepatocyte death by scavenging intracellular reactive oxygen species (ROS) and maintaining intracellular glutathione levels. Here, we examined the effects of ECP on the activities of alcohol-metabolizing enzymes and their regulating mechanisms in ethanol-treated hepatocytes. Isolated hepatocytes were incubated with or without 100 mM ethanol. ECP was dissolved in dimethylsulfoxide. ECP was added to cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Alcohol metabolism by CYP2E1 often generates large amounts of highly reactive, oxygen-containing molecules or reactive oxygen species (ROS), leading to exacerbated oxidative stress [96]. A study employing a polyphenol treatment as a means to suppress ethanol-induced hepatocyte death also demonstrated that cAMP modulated CYP2E1 and ADH activities, consequently leading to reduced ROS production and cell death [97]. …”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…Alcohol metabolism by CYP2E1 often generates large amounts of highly reactive, oxygen-containing molecules or reactive oxygen species (ROS), leading to exacerbated oxidative stress [96]. A study employing a polyphenol treatment as a means to suppress ethanol-induced hepatocyte death also demonstrated that cAMP modulated CYP2E1 and ADH activities, consequently leading to reduced ROS production and cell death [97]. …”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…ADH activity was measured as reported by Yamashita et al (2015). SDH activity was detected according to Landi et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, decreasing or inhibiting CYP2E1 activity may be a feasible strategy for minimizing the hepatotoxicity of ethanol. Recently, we demonstrated that Ecklonia cava polyphenol-treatment maintained CYP2E1 activity in ethanol-treated hepatocytes below that of control cells [23]. We also reported that treatment with an extract of Yerba Mate tea suppressed ethanol-induced increases in CYP2E1 activity to the level of the control cells in an in vitro, alcohol-induced hepatocyte model and an in vivo ethanol plus CCl 4 -induced liver-injury model [16].…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, cAMP-dependent phosphorylation of CYP2E1 lead to a reduction in CYP2E1 activity [28]. We have shown that the treatment of Ecklonia cava polyphenol with ethanol increased the activity of alcohol dehydrogenase and inhibits CYP2E1 activity [23]. The changes in CYP2E1 and alcohol dehydrogenase activity were suppressed by treatment with H89, an inhibitor of PKA, suggesting that Eclonia cava polyphenol has a protective effect against ethanol-induced liver injury in a cAMP-dependent manner.…”
Section: Discussionmentioning
confidence: 99%